Molecular Evidence for the Fitness of Cotton Aphid, Aphis gossypii in Response to Elevated CO2 From the Perspective of Feeding Behavior Analysis - Jiang, Shoulin; Dai, Yang; Lu, Yongqing; Fan, Shuqin; Liu, Yanmin; Bodlah, Muhammad Adnan; Parajulee, Megha N.; Chen, Fajun (Frontiers in Physiology, 2018)
Rising atmospheric carbon dioxide (CO2) concentration is likely to influence insect–plant interactions. Aphid, as a typical phloem-feeding herbivorous insect, has shown consistently more positive responses in fitness to elevated CO2 concentrations than those seen in leaf-chewing insects. But, little is known about the mechanism of this performance. In this study, the foliar soluble constituents of cotton and the life history of the cotton aphid Aphis gossypii and its mean relative growth rate (MRGR) and feeding behavior were measured, as well as the relative transcript levels of target genes related appetite, salivary proteins, molting hormone (MH), and juvenile hormone, to investigate the fitness of A. gossypii in response to elevated CO2 (800 ppm vs. 400 ppm). The results indicated that elevated CO2 significantly stimulated the increase in concentrations of soluble proteins in the leaf and sucrose in seedlings. Significant increases in adult longevity, lifespan, fecundity, and MRGR of A. gossypii were found under elevated CO2 in contrast to ambient CO2. Furthermore, the feeding behavior of A. gossypii was significantly affected by elevated CO2, including significant shortening of the time of stylet penetration to phloem position and significant decrease in the mean frequency of xylem phase. It is presumed that the fitness of A. gossypii can be enhanced, resulting from the increases in nutrient sources and potential increase in the duration of phloem ingestion under elevated CO2 in contrast to ambient CO2. In addition, the qPCR results also demonstrated that the genes related to appetite and salivary proteins were significantly upregulated, whereas, the genes related to MH were significantly downregulated under elevated CO2 in contrast to ambient CO2, this is in accordance with the performance of A. gossypii in response to elevated CO2. In conclusion, rise in atmospheric CO2 concentration can enhance the fitness of A. gossypii by increasing their ingestion of higher quantity and higher quality of host plant tissues and by simultaneously upregulating the transcript expression of the genes related to appetite and salivary proteins, and then this may increase the control risk of A. gossypii under conditions of climate change in the future.